Long-Term Nitrogen and Phosphorus Fertilization of Irrigated Grain Sorghum - A. Schlegel; H. D. Bond (Kansas Agricultural Experiment Station Research Reports, 2018)
This study was initiated in 1961 to determine responses of continuous grain sorghum grown under flood irrigation to N, P, and K fertilization. The study is conducted on a Ulysses silt loam soil with an inherently high K content. The irrigation system was changed from flood to sprinkler in 2001.
Keywords: Nitrogen fertilization; phosphorus fertilization; irrigated grain sorghum; long-term fertility; nutrient removal